PEDIATRIC OCULAR TRAUMA MANAGEMENT: A CASE STUDY OF EFFECTIVE INTRA-ORBITAL FOREIGN BODY IOFB EXTRACTION - Doni Setiawan; Liesa Z Subuh; Alexandria Stephanie Suparman; Yugos Juli Fitra (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: The rare nature of Orbitocranial Injury with Intraorbital Foreign Body (IOFB). Utilizing a 3D Head CT Scan to ascertain the precise location of the IOFB and its impact on anatomical structures is pivotal in shaping immediate treatment strategies, thereby reducing the potential for complications. Abstract: Introduction:  Penetrating intraorbital foreign body (IOFB) injuries are a rare form of traumatic injury. Recognized as a surgical emergency, meticulous history-taking and a thorough examination are essential for determining the trauma's mechanism and cause, facilitating accurate diagnosis and effective disease management. Case Illustration: In the emergency room, a 5-year-old female patient was presented with a craniofacial injury resulting from an IOFB. An evacuation procedure, conducted through a subsidiary incision, was performed to extract the foreign body. Interestingly, the object removed from the orbital cavity was a plastic foreign body, initially suspected to be a fractured orbital bone. Discussion: The clinical presentation, management, and outcomes of orbital foreign body injuries can differ based on the material composition of the foreign body. In cases of intraorbital foreign body trauma, the primary treatment goal is foreign body removal. Conclusion: Precise and accurate initial management in the emergency department is crucial. Early diagnosis, aided by a 3D head CT scan, is instrumental in locating the IOFB and identifying the involved anatomical structures. This, in turn, enables timely treatment decisions to minimize the risk of complications.